Five Freedoms and their Implications for a Less Developed National Economy - Čičinskas, Jonas (Ekonomika, 2004)
The article deals with the issue of the growing role of knowledge as a production factor and its implications for a national economic development. A review of liberalization of goods and services, capital and, however highly selective, labour movement leads to the conclusion that although liberalization extends possibilities for all participating countries to speed up their economic development it does not necessarily serve as an instrument for narrowing the development gap. Deep changes in production processes, linked with rapid changes in information and communication technologies, expose the growing role of knowledge which becomes a separate factor of production. Can knowledge play a role of a factor that could preferentially assist less developed countries in closing the gap in their economic and social evolution? The analysis shows that it rather cannot because the processes and procedures of international political economy are put in action for still the same economic and political goal - to preserve the leading role of developed countries in the global community. Less developed countries, including nations in transition, cannot rely on implementation of all five freedoms in cross-border economic relations, when they aim to narrow the developmental gap; special measures of economic policy. both on the national and international scale, are needed to solve the problem.